The Study of Infrastructures and Riparian Area at Krasak Watershed, Indonesia - Ikhsan, Jazaul; Hilmi, Ikhlassul; Harsanto, Puji; Nursetiawan, Nursetiawan (Universitas Negeri Semarang, 2019)
Debris flow that cause the eruption Merapi mount in 2010 caused damage at some infrastructure that is on the Krasak River. Some areas had gotten debris flow which was resulting break up the important access street that had been connecting between Yogyakarta and Magelang. Krasak river is one of the rivers that has upstream on the Merapi slope mount and also got impact of debris flow in 2010. This research is aimed to know condition of infrastructure and edge river at the Krasak river after got impact of debris flow. This research is using survey method that directly observes to the object of research for knowing condition infrastructure and edges river with survey form 123. The result of the research is showing some infrastructure river that is getting damage caused of cold lava. Debris flow had happened in the past, so some of infrastructure had been repairing. But there is some infrastructure still has little damage. However, the function of this infrastructure is showing good condition. Condition of edges river are still secure, it happens because the Krasak river had pass through regions plantation, but there is some locations of the settlement is in the riparian area or debris prone area.